Karakterisasi Rizobakteri yang Berpotensi Mengendalikan Bakteri Xanthomonas oryzae pv. oryzae dan Meningkatkan Pertumbuhan Tanaman Padi - . Agustiansyah; Satriyas Ilyas; Sudarsono .; Muhammad Machmud (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2013)
Characterization of rhizobacteri having potential to control Xanthomonas oryzae pv. oryzae and increase plant growth of rice. Rhizobacteria which are isolated from root could produce HCN, siderophore, and plant growth regulator, induce systemic resistance, and are increase uptake of plant nutrition such as phosphate. The objective of this research was to characterize rhizobacteri as controling agent for Xanthomonas oryzae pv.oryzae (Xoo) and as plant growth promoter. The results show that the isolates of P. diminuta A6, P. aeruginosa A54, B.subtilis 11 /C, and B. subtilis 5/B inhibited the growth of Xoo. B. subtilis 5/B isolate produced the highest siderophore activity, followed by of P. aeruginosa A54, P. diminuta A6 and B. subtilis 11/C. Only P. diminuta A6 isolate produced HCN. The results also showed that all rhizobacteri produced IAA i.e. B.subtilis 5/B (22.10 µg/ml), B. subtilis 11/C (19.05 µg/ml), P. diminuta A6 (8.68 ug/ml), and P. aeruginosa A54 (2.95 µg/ml). The content of phosphatase enzyme was as folows B.subtilis 5/B (2.78 units/ ml), B.subtilis 11/C (5.7 units/ml), P. diminuta A6 (2.25 units/ml), and P. aeruginosa A54 (5.71 units / ml). Content of peroxidase enzymes in plants that were treated by using isolates was as follows B.subtilis 5/B (1.30 x 10-3 units/mg protein), P. aeruginosa A6 (1.20 x 10-3 units/mg protein), B.subtilis 11/C (1.15 x 10-3 units/mg protein), and P. aeruginosa A54 (1.05 x 10-3 units/mg protein).